2022
DOI: 10.1002/arch.21897
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of PBAN receptor expression reduces fecundity in the fall armyworm, Spodoptera frugiperda

Abstract: The fall armyworm, Spodoptera frugiperda, native to the tropical and subtropical areas of the American continent is one of the world's most destructive insect pests. In most insects, sex pheromone production is initiated following the activation of a pheromone‐biosynthesis‐activating neuropeptide (PBAN) receptor, which belongs to G protein‐coupled receptor. We explored expression level of S. frugiperda PBAN receptor (Sf‐PBANr) gene and validated the physiological function by assessing the fecundity of adult fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…In addition, RNAi of PBAN expression led to reduced transcript levels associated with sex pheromone biosynthesis in Spodoptera liture 34 . Similarly, RNAi of PBAN receptor gene led to a significant reduction in fecundity, which presumably suppressed the pheromone biosynthetic machinery in S. frugiperda 35 . These sugggest that Fo-PBAN mediates the biosynthetic machinery by activating biosynthetic enzymes and up-regulating their gene expressions in the production of the aggregation pheromone.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, RNAi of PBAN expression led to reduced transcript levels associated with sex pheromone biosynthesis in Spodoptera liture 34 . Similarly, RNAi of PBAN receptor gene led to a significant reduction in fecundity, which presumably suppressed the pheromone biosynthetic machinery in S. frugiperda 35 . These sugggest that Fo-PBAN mediates the biosynthetic machinery by activating biosynthetic enzymes and up-regulating their gene expressions in the production of the aggregation pheromone.…”
Section: Discussionmentioning
confidence: 99%
“…Functional analyses of PBANR in moths have mainly demonstrated the reactivity of PBANR to PBAN. However, in a few species such as P. xylostella and S. frugiperda, the function of PBANR was analyzed after PBANR suppression by RNAi in the pheromone glands of female adults [16,47]. In this study, prior to RNAi treatment, we measured the diurnal expression of MviPBANR-C in response to MviPBAN in the pheromone glands of M. vitrata.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we focused on RNAi regions on PBANR sequences in three moth species. In the case of P. xylostella and S. frugiperda, RNAi was performed on the TM region containing ECL, which is important for ligand binding [16,47]. However, RNAi suppression was performed on the C-terminal tail of MviPBANR-C, which is different from that of MviPBANR-B.…”
Section: Discussionmentioning
confidence: 99%
“…The successful achievements in gene knockdown or silencing with significant adverse effects on reproduction make RNAi a promising tool against S. frugiperda. Recent studies have shown that the fertility and the total number of eggs laid per adult female of S. frugiperda were decreased by the particular regulation of Sf-PBANr (neuropeptide receptor activating pheromone biosynthesis) by RNA interference ( Park and Vatanparast, 2022 ). Therefore, it is advisable to improve RNAi efficiency by focusing on gene functional studies for the identification of key genes that govern S. frugiperda reproduction and ways of delivery to sustain its applicability.…”
Section: Methodsmentioning
confidence: 99%